Treatment of hepatitis C after kidney transplant: A pooled analysis of observational studies. Issue 6 (7th March 2014) - Fabrizi, Fabrizio; Penatti, Alessandra; Messa, Piergiorgio; Martin, Paul
<x xml:space="preserve">Abstract</x> Various authors have given IFN‐based therapy for hepatitis C among renal transplant recipients but the efficacy and safety of this approach remains unclear. A systematic review of the literature with a meta‐analysis of clinical studies was performed in order to assess efficacy and safety of antiviral therapy (IFN‐based therapy) in renal transplant recipients with hepatitis C virus infection. The primary outcomes were sustained virological response (as a measure of efficacy) and/or drop‐out rate (as a measure of tolerability). The random‐effects model of DerSimonian and Laird was used, with heterogeneity and sensitivity analyses. Sixteen studies (187 unique patients) were identified, one being controlled study. The summary estimate for sustained virological response and dropout rate was 0.34 (95% confidence intervals: 0.27, 0.42) and 0.32 (95% CI: 0.21, 0.44), respectively. The studies were heterogeneous with regard to dropout rate but not to sustained viral response. The most common side‐effect requiring interruption of treatment was graft dysfunction (n = 27; 51%). Stratified analysis reported a higher rate of drop‐outs in those studies based on IFN monotherapy (pooled event rate, 0.43; 95% CI: 0.25, 0.63). Meta‐regression analysis showed an inverse relationship between reference year (P = 0.019), length of IFN therapy (P = 0.029) and drop‐out rate. IFN‐based therapy has inadequate safety and tolerance after renal transplantation. The reasons for the high rate of graft dysfunction after IFN have not been fully elucidated. Antiviral treatment of hepatitis C among kidney graft recipients continues to be a challenge to transplant physicians. J. Med. Virol. 86:933–940, 2014. © 2017 Wiley Periodicals, Inc.